AB0766 Secukinumab provides sustained remission and low disease activity related to disease activity index for psoriatic arthritis (DAPSA): 2 year results from the future 2 study. (15th June 2017) - Smolen, JS; McInnes, IB; Kvien, TK; Pricop, L; Fox, T; Rasouliyan, L; Jugl, S; Gaillez, C; ,
Abstract : Background: Disease Activity Index for Psoriatic Arthritis (DAPSA) is a validated tool to measure disease activity states, focussing on peripheral joint involvement in psoriatic arthritis (PsA), and can be used to assess targets such as remission (REM) or low disease activity (LDA). 1 Objectives: Secukinumab, a fully human anti–interleukin-17A monoclonal antibody, significantly improved American College of Rheumatology responses vs. placebo at Week (Wk) 24 that were sustained through Wk 104 in active PsA patients (pts) in the FUTURE 2 study 2 . This post-hoc exploratory analysis assessed DAPSA states through Wk 104. Methods: In total, 397 active PsA pts were randomised to subcutaneous (s.c) secukinumab (300, 150 or 75mg) or placebo at baseline and Wks 1, 2, 3 and 4, and every 4 wks (q4w) thereafter. Placebo pts were re-randomised to secukinumab 300 or 150mg s.c q4w from Wk 16 or 24, depending on Wk 16 clinical response. DAPSA was derived as the sum of five variables: tender joint and swollen joint counts (TJC 68 and SJC 66); pt global and pain assessed on a 10cm visual analogue scale; and C-reactive protein levels (mg/dl) with validated cut-offs to indicate REM (≤4), LDA (>4 and ≤14), moderate disease activity (MDA; >14 and ≤28) and high disease activity (HDA; >28). DAPSA was assessed in the overall population and in pts stratified by prior anti-tumour necrosis factor (anti-TNF) therapy use (anti–TNF-naïve vs. inadequate response/intolerance to these agents [anti–TNF-IR]) and time since first PsA diagnosis (≤2 vs. >2 years) using observed data. Only data for secukinumab 300 and 150mg (approved doses) are reported. Results: Baseline demographics and clinical characteristics were similar across treatment groups and previously reported. 3 DAPSA score at baseline (mean [SD]) was 42.0 (17.4), 46.8 (24.3) and 44.9 (25.3) in the secukinumab 300mg, 150mg and placebo groups, respectively. In the overall population, at Wk 16, REM was achieved in 14/97 (14.4%) with secukinumab 300mg and 10/100 (10%) with secukinumab 150mg vs. placebo 4/87 (4.6%); LDA in 27/97 (27.8%) and 34/100 (34%) vs. 12/87 (13.8%), respectively. REM or LDA were sustained through Wk 104 with secukinumab 300 and 150mg (55/84 [65.5%; REM + LDA] and 41/ 77 [53.2%; REM + LDA], respectively). The proportion of pts achieving each DAPSA state at Wks 16 and 104 by anti-TNF status (anti–TNF-naïve vs. anti–TNF-IR) and by time since diagnosis (≤2 vs. >2 years) for secukinumab 300 and 150mg is presented in the figure. Conclusions: In the overall population, a higher proportion of pts treated with secukinumab at Wk 16 achieved DAPSA REM than those treated with placebo, with REM and LDA sustaining through Wk 104. At Wk 16, a higher proportion of anti–TNF-naïve pts treated with secukinumab achieved and sustained DAPSA REM than anti–TNF-IR pts and a higher proportion of pts with early diagnosis (≤2 years) achieved DAPSA REM vs. pts diagnosed later (>2 years). References: Schoels MM, et al. Ann Rheum Dis 2016;75:811–8. McInnes IB, et al. Arthritis Rheumatol 2016;68 (suppl 10). McInnes, et al. Lancet 2015;386:1137–46. Disclosure of Interest: J. Smolen Grant/research support from: AbbVie, Janssen, Eli Lilly, MSD, Pfizer, Roche, Amgen, AstraZeneca, Astro, Celgene, Celltrion, GSK, ILTOO, Medimmune, Novartis-Sandoz, Pfizer, Samsung, Sanofi and UCB., Consultant for: AbbVie, Janssen, Eli Lilly, MSD, Pfizer, Roche, Amgen, AstraZeneca, Astro, Celgene, Celltrion, GSK, ILTOO, Medimmune, Novartis-Sandoz, Pfizer, Samsung, Sanofi and UCB., I. McInnes Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB., Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB., Speakers bureau: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB., T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB., Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB., L. Pricop Shareholder of: Novartis, Employee of: Novartis, T. Fox Shareholder of: Novartis, Employee of: Novartis, L. Rasouliyan Consultant for: Novartis through employment at RTI, Employee of: RTI Health Solutions, S. Jugl Shareholder of: Novartis, Employee of: Novartis, C. Gaillez Shareholder of: Novartis and BMS, Employee of: Novartis